New Class of Close-to-Convex Harmonic Functions Defined by a Fourth-Order Differential Inequality - Mohammad Faisal Khan; Khaled Matarneh; Shahid Khan; Saqib Hussain; Maslina Darus (Journal of Mathematics)
In the recent past, various new subclasses of normalized harmonic functions have been defined in open unit disk U which satisfy second-order and third-order differential inequalities. Here, in this study, we define a new class of normalized harmonic functions in open unit disk U which is satisfying a fourth-order differential inequality. We investigate some useful results such as close-to-convexity, coefficient bounds, growth estimates, sufficient coefficient condition, and convolution for the functions belonging to this new class of harmonic functions. In addition, under convex combination and convolution of its members, we prove that this new class is closed, and we also give some lemmas to prove our main results.